Pseudoepitheliomatous hyperplasia: The link between sporotrichosis and squamous cell carcinoma (Research, Society and Development, 2022)
The pseudoepitheliomatous hyperplasia (PEH) is a benign condition. It is a reactive histological pattern characterized by hyperplasia of the epidermis and adnexal epithelium. Therefore, it can be found in several clinically heterogeneous diseases: Infections, neoplasms, dermatoses with inflammation/chronic irritation, and miscellaneous processes. Among the infections group, deep mycoses stand out, and squamous cell carcinoma (SCC) for the neoplasm. As these two lesions can be observed in the same body regions and present visually similar features, it is also natural that they can be mistaken, as seen in previous works. Thus, we propose an individually based, cross-sectional retrospective review of patients with confirmed sporotrichosis (from a total of 86 cutaneous sporotrichosis cases) in which squamous cell carcinoma was also suspected as a clinical hypothesis. Considering the small sample, a qualitative analysis of the results was made. This paper presents an explanation with a microscopic basis for this diagnostic error. We also recommend examining several histological sections, detailed clinical information, and the use of special stains to avoid misdiagnosis.